KHITAN PEREMPUAN DALAM PERSPEKTIF ETIKA KEDOKTERAN, REGULASI MEDIS DAN HUKUM ISLAM DI INDONESIA - Amalia Yuliana Shakira; Mutiara Anissa (Yayasan Nusantara Hasana Berdikari, 2025)
Female circumcision or Female Genital Mutilation (FGM) remains a prevalent traditional practice in Indonesia despite having no medical benefits and potentially causing various health complications. This study aims to analyze the practice of female circumcision from three main perspectives: medical ethics, medical regulations, and Islamic law in Indonesia. The research methodology employed a systematic literature review of 20 selected articles from PubMed, ScienceDirect, and Google Scholar databases published between 2015-2025. The results indicate that female circumcision causes various negative impacts including bleeding, infections, psychological trauma, and obstetric complications. Regulatory-wise, Indonesia has revoked the permission for this practice through Ministry of Health Regulation No. 6/2014, but its implementation still faces challenges due to socio-cultural factors and diverse religious interpretations. From the Islamic law perspective, the study found no consensus among scholars regarding the obligation of female circumcision, and the practice is more driven by tradition than strong religious doctrines. This study concludes the need for a multidisciplinary approach integrating health, legal, and socio-cultural aspects to effectively address the issue of female circumcision.